Technical analysis, contestation and politics in policy agenda setting and implementation: the rise and fall of primary care maternal services from Ghana's capitation policy. Issue 1 (December 2016) - Koduah, Augustina; van Dijk, Han; Agyepong, Irene
Abstract Background Why issues get on the policy agenda, move into policy formulation and implementation while others drop off in the process is an important field of enquiry to inform public social policy development and implementation. This paper seeks to advance our understanding of health policy agenda setting, formulation and implementation processes in Ghana, a lower middle income country by exploring how and why less than three months into the implementation of a pilot prior to national scale up; primary care maternal services that were part of the basket of services in a primary care per capita national health insurance scheme provider payment system dropped off the agenda. Methods We used a case study design to systematically reconstruct the decisions and actions surrounding the rise and fall of primary care maternal health services from the capitation policy. Data was collected from July 2012 and August 2014 through in-depth interviews, observations and document review. The data was analysed drawing on concepts of policy resistance, power and arenas of conflict. Results During the agenda setting and policy formulation stages; predominantly technical policy actors within the bureaucratic arena used their expertise and authority for consensus building to get antenatal, normal delivery and postnatal services included in the primary care per capita payment system. Once policy implementation started, policy makers were faced with unanticipated resistance. Service providers, especially the private self-financing used their professional knowledge and skills, access to political and social power and street level bureaucrat power to contest and resist various aspects of the policy and its implementation arrangements – including the inclusion of primary care maternal health services. The context of intense public arena conflicts and controversy in an election year added to the high level political anxiety generated by the contestation. The President and Minister of Health responded and removed antenatal, normal delivery and postnatal care from the per capita package. Conclusion The tensions and complicated relationships between technical considerations and politics and bureaucratic versus public arenas of conflict are important influences that can cause items to rise and fall on policy agendas.